Combination of echocardiography with systemic hemodynamic parameters for early risk stratification of hemodynamically significant patent ductus arteriosus in preterm infants - Chen, Cuie; Cui, Yuechong; Chen, Shujun; Chen, Jiaonv; Zhao, Lirong; Sun, Yuanyuan; Ji, Liuqing; Wang, Guoliang (Frontiers in Pediatrics, 2025)
BackgroundHemodynamically significant patent ductus arteriosus (hsPDA) is a major contributor to morbidity and mortality in extremely preterm infants. Both echocardiographic assessment and systemic hemodynamic monitoring have emerged as valuable tools for evaluating cardiovascular status during the early postnatal period. This study aimed to evaluate whether echocardiographic and systemic hemodynamic parameters within 72 hours can predict the development of hsPDA in preterm infants.MethodsIn this prospective study, 98 infants born at our institution between October 2022 and March 2025 were enrolled based on inclusion criteria of gestational age ≤32 weeks and birth weight ≤1,500 g. Hemodynamic monitoring was conducted using the Non-Invasive Cardiac System (NICaS) at 24, 48, and 72 hours after birth, each followed immediately by echocardiographic evaluation.ResultsAmong 98 preterm infants, 85 had patent ductus arteriosus (PDA) at 24 hours, with 30 progressing to hsPDA. The hsPDA group had significantly lower gestational age and birth weight. Maternal eclampsia or preeclampsia, placental abruption, neonatal asphyxia, alveolar surfactant need, mechanical ventilation within 72 hours, and higher fluid intake in the first 24 hours were more frequent in this group. These infants required prolonged respiratory support and parenteral nutrition, and showed higher rates of intraventricular hemorrhage (IVH) and bronchopulmonary dysplasia (BPD). Compared to non-hsPDA infants, those with hsPDA had larger ductus arteriosus (DA) diameters, higher DA diameter/weight ratios at 48 and 72 hours, and elevated left atrium-to-aortic root (LA/Ao) ratios at 24, 48, and 72 hours. Stroke index (SI), cardiac output index (CI), and total body water percent (TBW%) were increased, while total peripheral resistance index (TPRI) was reduced at 48 and 72 hours. Multivariate analysis identified maternal eclampsia/preeclampsia, surfactant use, DA diameter-to-weight ratio, LA/Ao, and TBW% at 48 and 72 hours as independent risk factors. A combined model achieved high predictive accuracy (AUC = 0.981, sensitivity = 100%, specificity = 90.0%).ConclusionThis study demonstrated that combining echocardiographic parameters with systemic hemodynamic indicators at 72 hours of life provides significant predictive value for identifying preterm infants with a gestational age ≤32 weeks and birth weight ≤1,500 g who are at risk of developing hsPDA.